CC Genotype at TCF7L2 Diabetes Risk Locus rs7903146 Directs a Coordinated Fatty Acid Response to a Mediterranean Diet Intervention: A Randomized Controlled Trial - Laurence D. Parnell; Chao-Qiang Lai; Christina Holzapfel; Jacob J. Christensen; José M. Ordovás (Lifestyle Genomics)
Introduction: Previous studies identified genetic links between the TCF7L2 C/T variant rs7903146, type 2 diabetes (T2D), and obesity. We wished to deepen our understanding of how specific diets interact with this variant to affect blood metabolites, an aspect not previously investigated. Hence, we conducted a controlled study where individuals with different genotypes followed a Mediterranean (Med) or low-fat (LF) diet for 1 week. Methods: Participants were recruited from the Boston, MA (USA) area. Anthropometric and clinical measures were taken. Genotypes at rs7903146 were ascertained, with homozygous carriers of the more common and protective CC or risk TT genotype invited to participate. Participants followed both diets (LF or Med) for 1 week with ∼10 days’ washout between diets. Blood samples taken at the beginning and end of each diet period underwent metabolomics analysis using nuclear magnetic resonance spectroscopy. We evaluated how the diet affected different metabolites based on genetic profile. Results: The cohort of 35 persons was 43% female, aged 18–70 y, with BMI between 26.4 and 33.9 kg/m2. Focusing on fatty acids (FAs) and other lipid metabolic factors (n = 23), we observed a greater number and stronger correlations among these factors in the CC genotype-Med diet group than in the other three genotype-diet combinations. An aggregate of 11 factors, each negatively correlating with delta-saturated fatty acids (SFA), showed a significant genotype-Med diet interaction on delta-SFA in CC individuals on the Med diet (p = 0.0046). A similar genotype-Med diet interaction was observed for delta-monounsaturated fatty acids (p = 0.0078). These interactions were not statistically significant at the end of the LF intervention. Conclusion: Our findings suggest that the Med diet has a stronger influence on regulating lipid factors in individuals with the CC genotype at the TCF7L2 variant rs7903146. This diet-genotype interaction may have significant implications for understanding the inter-individual variation of metabolic response on specific dietary regimens.